Can coefficient of variation of time-domain analysis be valuable for detecting cardiovascular autonomic neuropathy in young patients with type 1 diabetes: a case control study. Issue 1 (December 2017) - Razanskaite-Virbickiene, Dovile; Danyte, Evalda; Mockeviciene, Giedre; Dobrovolskiene, Rimante; Verkauskiene, Rasa; Zalinkevicius, Rimantas
Abstract Background Cardiovascular autonomic neuropathy (CAN) increases morbidity and mortality in diabetes through association with a high risk of cardiac arrhythmias and sudden death, possibly related to silent myocardial ischemia. During the sub-clinical stage, CAN can be detected through reduction in heart rate variability (HRV). The aim of our study was to estimate if the time and frequency-domain analysis can be valuable for detecting CAN in young patients with type 1 diabetes mellitus (T1DM). Methods For this case control study of evaluation of cardiovascular autonomic function the 15–25 years age group of patients with duration of T1DM more than 9 years (n  = 208, 89 males and 119 females) were selected. 67 patients with confirmed CAN were assigned to the "case group" and 141 patients without CAN served as a control group, the duration of T1DM was similar (15.07 ± 4.89 years vs.13.66 ± 4.02 years;p  = 0.06) in both groups. Cardiovascular autonomic reflex tests and time and frequency domains analysis of HRV were performed for all subjects. Results Time domain measures were significantly lower in CAN group compared with control (p  < 0.05). R-R max / R-R min ratio and coefficient of variation (CV) were the lowest during deep breathing among T1DM patients with CAN. Receivers operating characteristic (ROC) curves were constructed to compare the accuracies of the parameters of time-domain analysis for diagnosing CAN. We estimated a more reliable cut-off value of parameters of time-domain. The CV values in supine position <1.65, reflected sensitivity 94.3%, specificity 91.5%. The CV values during deep breathing <1.45 reflected sensitivity 97.3%, specificity 96.2%. The CV values in standing position <1.50 reflected sensitivity 96.2%, specificity 93.0%. The most valuable CV was during deep breathing (AUC 0.899). The results of frequency-domain (spectral analysis) analysis showed significant decrease in LF power and LFPA, HF Power and HFPA, total power among subjects with CAN than compared with subjects without CAN (p  < 0.05). Conclusions Time and frequency domain analysis of HRV permits a more accurate evaluation of cardiovascular autonomic function, providing more information about sympathetic and parasympathetic activity. The coefficient of variation (time-domain analysis) especially during deep breathing could be valuable for detecting CAN.